Algoritmo de sincronização com detector de sequência positiva e negativa: aplicação em conversores estáticos conectados à rede elétrica - Fonseca, Jean Marcos Lobo da (2019)
This work is a follow up two synchronization algorithms with applications to grid-connected power converters. The first structure is a positive sequence detector with good performance in scenarios with high harmonic distortion. The second one, also known as ISI-PLL, adds an adaptive filter to the first structure in order to enhance its filtering capability in scenarios with subharmonic and interharmonic distortion. This work proposes to expand both structures so that they are able to detect negative sequence components as well. The negative sequence components can be used as a mechanism to protect the converter or to control it in scenarios with grid-voltage imbalance. Then, the structure is expanded once again in order to detect, in real time, any harmonic component in the input signal. Simulation results are obtained using the software MATLAB/SIMULINK whereas experimental results are obtained with the aid of the HIL DSPACE platform. The results involve the comparison between two well-known synchronization algorithms and the two proposed structures and suggest their equivalence or even superiority in multiple scenarios. Aiming to prove the applicability of the proposed structures, they are employed in the control structure of a grid-connected power converter that operates as a STATCOM. The converter objectives are grid-voltage regulation at the point of common coupling, power factor correction and canceling of oscillating reactive power components in scenarios with grid-voltage imbalance. Simulation results are carried out using the software PSCAD/EMTDC and experimental results are obtained using, again, the HIL DSPACE platform, with the aid of the electronic control unit ControlDesk.